2006
DOI: 10.1111/j.1399-0039.2006.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

OAS1 gene haplotype confers susceptibility to multiple sclerosis

Abstract: Multiple sclerosis (MS) is associated with genetic susceptibility and unknown environmental triggers, possible viral infections, but the specific etiological mechanism that subsequently develops into an inflammatory/autoimmune cascade of events is poorly understood. Recently, genetic variants of 2',5'- oligoadenylate synthetase 1 (OAS1) gene, a critical enzyme involved in innate antivirus response, have been associated with differential enzyme activity and type 1 diabetes in both case-control and family studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 23 publications
3
49
1
Order By: Relevance
“…The most significant probe set can hybridize only to the extended transcript variant and can thus differentiate between them; as shown in Figure 2A, not a single CEPH individual overlaps in expression level of this probe set between genotypes (P < 10 À89 ). OAS1 is an enzyme involved in innate antiviral response with splice variants that are known to affect susceptibility to viral infection (Bonnevie-Nielsen et al 2005) and multiple sclerosis (Fedetz et al 2006). The same splice site SNP known to associate with disease susceptibility was recently shown also to associate with splicing of OAS1 in CEPH cell lines (Kwan et al 2007), a finding that is confirmed by our analysis (Supplemental Fig.…”
Section: Polymorphisms Influencing Ptvsupporting
confidence: 78%
See 3 more Smart Citations
“…The most significant probe set can hybridize only to the extended transcript variant and can thus differentiate between them; as shown in Figure 2A, not a single CEPH individual overlaps in expression level of this probe set between genotypes (P < 10 À89 ). OAS1 is an enzyme involved in innate antiviral response with splice variants that are known to affect susceptibility to viral infection (Bonnevie-Nielsen et al 2005) and multiple sclerosis (Fedetz et al 2006). The same splice site SNP known to associate with disease susceptibility was recently shown also to associate with splicing of OAS1 in CEPH cell lines (Kwan et al 2007), a finding that is confirmed by our analysis (Supplemental Fig.…”
Section: Polymorphisms Influencing Ptvsupporting
confidence: 78%
“…Two of these (IRF5 and OAS1), the two top hits genome-wide ( Fig. 2A,B; Table 1), have already been convincingly associated with both polymorphic splicing and other autoimmune diseases (Fedetz et al 2006;Graham et al 2007;Kozyrev et al 2007), so their unreplicated associations with RA and CD are quite plausible (and previous work supports the IRF5-RA association as well) ). For the four replicated disease SNPs, we implicate four genes that are all good functional candidates: ERAP1, PTPN2, CLEC2D, and TRAF1.…”
Section: Ptv In Complex Diseasesmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, EAE-susceptible mice are prone to developing the site of exon 7 and the "A" allele of a SNP in exon 3, has been linked to increased OAS1 enzyme activity as well as MS and type 1 diabetes susceptibility. [68][69][70][71] Importantly, different alternatively spliced mRNA isoforms are produced depending on which allele is present at the 3' splice site of exon 7. 69 However, functional data establishing the role of these alternative splicing products and their corresponding protein counterparts in susceptibility to MS are lacking.…”
Section: Ctla-4: a General Marker Of Autoimmunity?mentioning
confidence: 99%